Homeostasis Changes of Tear-Producing System with the Background of Cosmetic Procedures in Periorbital Area - V. N. Trubilin; E. G. Poluninа; D. V. Andzhelova; V. V. Kurenkov; S. G. Kapkova; K. V. Chinenova (Oftalʹmologiâ)
Modern ophthalmological practice is inseverable linked with cosmetology and esthetic medicine. Every year, the number of patients, especially women, who received various types of cosmetology procedures (botulinum toxin injections, eyelash extensions, eyelid tattooing, dermal fillers injections, etc.) in facial area increases, in particular in the periorbital zone. Purpose: to conduct a comprehensive assessment of clinical and functional parameters characterizing the state of the ocular surface and the tear-producing system in case applying cosmetic procedures in the periorbital area (Botox injections, eyelid tattooing, eyelash extension). Patients and methods. The study included 106 women (212 eyes). Exclusion criteria: early postoperative period after ophthalmosurgical intervention, acute inflammatory diseases of anterior and posterior eye segment, glaucoma, the presence of intraocular pathological changes (hemophthalmia, detachment of the eye membranes, tumors). The average age of the patients included in the study was 36.37 ± 9.0 years. Results and discussion. The results of a comparative evaluation of two groups of patients — a group with a history of cosmetic procedures (tattooing the eyelids, botulinum toxin, dermal fillers, eyelash extensions) in the periorbital zone and patients who did not use such procedures, has showed that cosmetic procedures affect on the clinical and functional eye surfaces state and on morphofunctional state of meibomian glands. Thus, the frequency of detection of symptomocomplex of dry eye syndrome was on 36 % more often determined in the group of patients received cosmetic procedures. It has been shown that the combined effect of cosmetological procedures (tattooing the eyelids, eyelash extensions, injections of dermal fillers and botulinum toxin in the periorbital region) aggravates the course and prognosis of Dry Eye Syndrome and meibomian glands dysfunction. A direct correlation between the severity of complaints characteristic of Dry Eye Syndrome and the number of procedures was found (r = 0.4982, p = 0.0000); the frequency of detecting complaints of dryness and discomfort and the number of procedures (r = 0.6427, p = 0.0000); compression test indices and the number of procedures (r = –0.4712, p = 0.0000); the frequency of occurrence of inflammatory reactions of ocular surface and the number of procedures (r = 0.3778, p = 0.0001). The risk of tear production disturbance — dry eye syndrome and dysfunction of the meibomian glands is higher in patients using botulinum toxin injections and eyelash extension in comparison with patients using eyelid tattooing and injections of fillers with hyaluronic acid in the periorbital zone.